Legalisasi Ganja Medis (Analisis Putusan MK Nomor 106/Puu-Xviii/2020) - Erik Dwi Prassetyo (Jurnal Analisis Hukum, 2022)
Indonesia is a state of law, the basic law for all laws and regulations in Indonesia is the 1945 Constitution of the Republic of Indonesia. In an effort to uphold the constitution and the principles of a democratic rule of law, the Constitutional Court has the authority to examine laws on the 1945 Constitution of the Republic of Indonesia. This study aims to knowing how the judges of the Constitutional Court considered the decision Number 106/PUU-XVIII/2020 and to find out the impact of the decision. This study uses a normative juridical approach with a descriptive analytical method which will explain the description of the analysis of the data that has been collected. Based on the results of the research on Decision Number 106/PUU-XVIII/2020 it can be concluded that the judges of the Constitutional Court in their consideration have not fully fulfilled the aspects of justice and legal expediency and are more inclined to original intent and do not reflect contextual meaning. Broadly speaking, there are four impacts of the decision, among others, the existence of legal certainty, closing the opportunity for re-testing, the government must conduct research on the use of marijuana, and determine the next policy in the hands of the House of Representatives.